Pengaruh Brand Equity dan Country Of Origin terhadap Customer Behavior Dalam Memilih Smartphone pada Sma Negeri 5 Kota Sukabumi - Mariati Tirta Wiyata; Aida Nuraeni (Institut Manajemen Wiyata Indonesia & Asosiasi Peneliti Manajemen Indonesia, 2021)
This study aims to determine the effect of brand equity and country of origin on customer behavior. This study uses a survey method, with a correlational approach. The location of the research was carried out in 5 Snenior High School in Sukabumi City with the entire population of class 12. Sampling using purpose sample technique as many as 169 out of 290 population by collecting data using quizonoer. The analysis technique uses descriptive analysis, multiple linear regression analysis, F test and t test. The results stated that the Brand Equity variable had no significant effect on Customer Behavior with a significance value of 0.120 (p> 0.05). Furthermore, based on the results of research conducted for the Country of Origin variable, the above shows the value of Sig. amounting to 0,000 (p <0.05), therefore the hypothesis is accepted, meaning that the Country of Origin variable has a significant effect on Customer Behavio. Then it is known that Brand equity and Country of origin if together will have a significant effect on customer behavior with a value of 396.415 r and Sig. F is 0,000 (p <0,05). So it can be concluded that brand equity and country of origin can influence customer behavior in choosing a brand of handphone.